The Validity of Power of Attorney Burdens the Rights of Liability in the Auction of Dependants' Rights - Pratomo, Bobby Hindratno; Sulastri, Sulastri (Universitas Islam Sultan Agung, 2023)
Right of Liability is a security right imposed on land rights as referred to in the Basic Agrarian Law. An authentic deed is an act done in the form required by law. One of these authentic deeds is the Power of Attorney to Impose Dependent Rights (SKMHT), if there is a forgery related to SKMHT in the dependent rights auction process that can cause the cancellation of the dependent rights auction, it needs to be questioned how strong SKMHT is before the law. This type of research is normative juridical research with the theory of legal certainty. Making SKMHT carried out by notaries is required to comply and obey legal provisions which are bound by making authentic deeds as stated and regulated in the Law on Rights of Dependents. The making of SKMHT is bound to certain requirements and forms that have been stipulated in laws and regulations. If certain requirements and forms are not fulfilled, then in accordance with the Explanation to Article 15 paragraph (1) of Law 4/1996, such a